Training on Utilizing Goat Manure into Kohe Fertilizer in vercoming Environmental Pollution in Negarasaka Village - Ulfah Izdihar; Nurbaiti; Ayu Rahayu Saraswati; Aditya Wahyu Nugraha; Elsa Windiastuti (Jurnal ETAM, 2025)
Negarasaka Village, located in Negeri Katon Subdistrict, Pesawaran Regency, Lampung Province is an area with high agricultural potential through its farming and livestock sectors. However, livestock activities generate significant waste, which, if not properly managed, can lead to environmental pollution. The utilization of livestock manure as compost has not been optimized, prompting the implementation of a socialization and workshop program on compost-making to improve community knowledge in Negarasaka Village. This activity involved 30 participants and employed methods such as material presentation, hands-on practice, and evaluation through pre-test and post-test to measure the effectiveness of the socialization program using questionnnaires. The result showed an increase in participants knowledge about compost by 77-100% regarding the concept, benefit and methods of compost produstion.